MEASURING THE AESTHETICS OF PHOTOGRAPHIC COMPOSITION USING CARTESIAN COORDINATE APPROACH TO PROVE VISUAL BALANCE - Prasetyo, Martinus Eko; Resmika, Ika (Institut Seni Indonesia Yogyakarta, 2024)
Photography is used for creative and reflective purposes, much like in fine art photography. The main goal of photographic aesthetics is to produce works that are not only technically sound but also have high artistic value. The research method used is qualitative descriptive. This study aims to measure the aesthetics of composition in photography with a focus on proving visual balance. Composition aesthetics are studied through the analysis of elements such as the golden ratio, symmetry, and tonal distribution. The research method involves collecting and analyzing data from sample photos with various compositions. The results show that visual balance can be measured using mathematical approaches and aesthetic principles, which influence the perception of beauty in a photo. The implications of this research are to strengthen understanding of how visual composition affects aesthetic judgment in photography. This research produces measures of aesthetic visual balance composition that will elevate case studies of six photographs from six professional photographers of different genres, whose works are internationally recognized, namely the works of photographers Natalie Dybisz, Lee Jeffries, Jimmy Nelson, Ansel Adams, Dorothea Lange, and Robert Capa, which will be measured visually using a three-to-two basic framing grid approach.